EFFECTS OF FLEXIBLE WORK ARRANGEMENTS ON ETHICAL DECISION MAKING: JOB SATISFACTION AS A MEDIATOR - Tiara Veronika Simamora; Martina Dwi Mustika; Bertina Sjabadhyni (Jurnal Psikologi TALENTA, 2019)
Abstract. Ethical Decision Making (EDM) is behavior that is based on cognitive morals to choose an ethical decision. Flexible Work Arrangement (FWA) is a work option that allows employees to be flexible in terms of the place of work and its settlement. Job satisfaction is a positive feeling about work. This study will see job satisfaction mediates flexible work arrangement relationships with ethical decision making. This research method is a survey with a cross sectional design. The sample in this study were those who had worked in Indonesia with simple random sampling. The results of the study point out a significant indirect effect of flexible work arrangement on ethical decision making through job satisfaction